2023
DOI: 10.1002/bsd2.290
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the sustainable development of firms: The moderating role of transformational leadership and firm size

Nabeel Rehman,
Nauman Majeed,
Muhammad Umair Javaid
et al.

Abstract: Due to escalating environmental problems and challenges, ensuring sustainable development (SD) has become a matter of concern for organizations worldwide at a precinct scale. This study aims to integrate the variables, which are antecedents of SD through direct and indirect paths. The managers as participants of small‐ and medium‐sized enterprises have helped the researchers to explore the role of green knowledge management (GKM) and green dynamic capacity with the intervention of green innovation and competit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 98 publications
0
1
0
Order By: Relevance
“…The focus here is exactly on the 20 documents [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] extracted from Scopus and WoS databases at the date of the research and combined through R Studio coding. The keywords of these publications have been analyzed by the bibliometric analysis software and offered the different conceptual visual snapshots above.…”
Section: Peer Reviewmentioning
confidence: 99%
“…The focus here is exactly on the 20 documents [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] extracted from Scopus and WoS databases at the date of the research and combined through R Studio coding. The keywords of these publications have been analyzed by the bibliometric analysis software and offered the different conceptual visual snapshots above.…”
Section: Peer Reviewmentioning
confidence: 99%
“…Although the role of sustainable leadership in enhancing sustainable performance has been confirmed by many studies (e.g., Iqbal et al, 2020, 2022; Nartgün et al, 2020), there is a lack of research on the moderating role of sustainable leadership especially, on the association between SPM and SPS. However, many researchers examined other types of leadership (ethical, transformational, and servant) as moderators on different relationships in various contexts and found that their proposed type of leadership positively moderated the proposed relationships in these studies (Bouichou et al, 2022; Li et al, 2021; Rehman et al, 2023). Moreover, Chen et al (2023) revealed that leadership support positively moderates the association of technological advancement, green supply chain management, and knowledge management with sustainable business performance.…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 99%
“…For example, Li et al (2021) found that ethical leadership positively moderates the association between green behavior intentions and employee green behavior. Rehman et al (2023) revealed that the relationship between green knowledge management and sustainable development is positively moderated by transformational leadership. Bouichou et al (2022) found that responsible leadership positively moderates the linkage between social corporate responsibility and employee commitment, engagement, and organizational citizenship behavior.…”
Section: Introductionmentioning
confidence: 99%